Porphyromonas gingivalis oral infection promote T helper 17/Treg imbalance in the development of atherosclerosis - Jie Yang; Juan Wu; Rui Zhang; Min Yao; Yu Liu; Leiying Miao; Weibin Sun (Elsevier, 2017)
Background/purpose: Increasing studies have indicated the involvement of Porphyromonas gingivalis in atherosclerosis. T helper 17 (Th17)/Treg balance is critical during atherosclerosis. However, whether P. gingivalis oral infection is associated with Th17/Treg imbalance is unclear. The aim of the present study was to investigate the effect of P. gingivalis on Th17/Treg balance during atherosclerosis. Materials and methods: ApoE-/- and C57BL/6 mice were inoculated orally with P. gingivalis ATCC 33277 for 9 weeks. The alveolar bone loss was assessed by microcomputerized tomography. The area of atherosclerosis plaque was identified by oil red O staining. Plaque stability was analyzed by CD68 and αSMA immunohistochemistry staining and Masson staining. The frequency of Th17 and Treg in spleen was detected by flow cytometry. The mRNA expression of Th17- and Treg-related factors was determined by quantitative polymerase chain reaction. Interleukin (IL)-6, a critical factor in modulating T-cell differentiation, was determined from spleen cells and mouse dendritic cells by enzyme-linked immunosorbent assay. Results: Long-term P. gingivalis oral infection induced alveolar bone resorption. In ApoE-/- mice, P. gingivalis enhanced atherosclerotic lesion formation and plaque instability accompanied with a decreased Treg frequency and an increased Th17 cell frequency. In addition, mRNA expression of retinoic acid receptor-related orphan receptor γt and IL-17 was increased, and that of transforming growth factor (TGF) β and IL-10 was decreased in P. gingivalis-infected ApoE-/- mice. Furthermore, secretion of IL-6 was elevated in the spleen of P. gingivalis-infected ApoE-/- mice, as well as in mouse dendritic cells after P. gingivalis infection. Conclusion: P. gingivalis oral infection may promote Th17/Treg imbalance by influencing T-cell differentiation during the process of atherosclerosis, with a larger lesion area and decreasing plaque instability.